2018
DOI: 10.1039/c8cc00394g
|View full text |Cite
|
Sign up to set email alerts
|

A bio-inspired homogeneous graphene oxide actuator driven by moisture gradients

Abstract: An actuator driven by moisture gradients has been developed from a homogeneous graphene oxide film, relying on the in situ formation of a bilayer structure induced by water adsorption. This actuator shows efficient and controllable bending motions, coupled with the capability of lifting objects 8 times heavier than itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
91
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 24 publications
4
91
1
Order By: Relevance
“…GO and CNa showed maximum bending angles of 13° and 34°, respectively. The value observed for GO was lower with respect to the data reported in literature, due to the lower operating temperature and to the larger thickness of our films. Increasing contents of CNa in the hybrid systems induced a remarkable increase of bending, as CNa/GO 20/80 and CNa/GO 40/60 showed bending angles of about 40° and 35°, respectively.…”
Section: Resultscontrasting
confidence: 87%
See 2 more Smart Citations
“…GO and CNa showed maximum bending angles of 13° and 34°, respectively. The value observed for GO was lower with respect to the data reported in literature, due to the lower operating temperature and to the larger thickness of our films. Increasing contents of CNa in the hybrid systems induced a remarkable increase of bending, as CNa/GO 20/80 and CNa/GO 40/60 showed bending angles of about 40° and 35°, respectively.…”
Section: Resultscontrasting
confidence: 87%
“…Qualitative assessments of the bending capability of GO, CNa, and hybrid films indicated that all of them quickly deflected upward (within seconds) once placed on a bare palm, whereas they did not bend when placed on dry substrates. The bending is well explained by a difference of relative humidity between the two sides of the film, which generates a bilayer‐like structure in terms of moisture gradient induced in the direction perpendicular to the film surfaces . A schematic representation of this phenomenon is depicted in Figure a, where a hybrid film section is constituted by orange and black rectangles, representing respectively CNa and GO platelets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, our group reported an actuator driven by the moisture gradients of a homogeneous graphene oxide (GO) film, due to the in situ formation of a bilayer structure caused by water adsorption (Figure ). This actuator displays fast and controllable bending motions, along with the ability to lift objects eight times heavier than its own weight . Because the materials are largely abundant and cost effective, humidity actuators will open the path to more abilities in smart textiles and soft robotics.…”
Section: Actuation Mechanismsmentioning
confidence: 99%
“…In recent years, the demand for smart actuators based on flexible intelligent driving materials has increased [1][2][3][4]. The role of flexible intelligent driving materials is to convert external stimuli (such as light, heat, humidity, magnetic field/electric field) into executable actions or signals needed by processors through rapid, reversible and controllable structural/morphological changes [5][6][7][8][9][10][11][12][13][14][15][16]. Flexible smart actuators driven by these stimuli have significant advantages in the soft robot, electronic skin, bionic technology and other fields [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%